MERANCANG MODEL PEMBELAJARAN MULTIKULTURAL DAN EMPATI SOSIAL UNTUK MENINGKATKAN PRESTASI BELAJAR PADA MATA KULIAH TELAAH PENGEMBANGAN KURIKULUM BAGI MAHASISWA PGSD FKIP UNIB - Sri Ken Kustianti, (Pendidikan Sekolah Dasar, 2011)
This study aims to (1) improve the quality of the learning process for faculty and students in a subject PGSD Studies Curriculum Development, through the implementation of the learning design of multicultural and social empathy. (2) Improve student achievement in a subject PGSD Studies Curriculum Development through the implementation multicultural learning design and social empathy. The problem: Does the application of the learning design of multicultural and social empathy can improve the quality of the learning process at the Curriculum Development Review courses for lecturers and students PGSD FKIP Unib? (2). Does the implementation of multicultural learning design and social empathy can improve learning achievement on the Curriculum Development Review courses for students PGSD FKIP Unib. To achieve this goal used method of classroom action research in collaboration with faculty as a researcher, designed by model cycles and analyzed through descriptive, qualitative. The subject involved two lectures in Curriculum Development Studies and 40 students of third semester PGSD FKIP Unib. Results showed the application of learning design multicultural and social empathy can improve the quality of the learning process of student group discussions of productivity in terms of frequency of involvement of members of the group in discussion, effectiveness and quality of communication of ideas / questions, make effective contributions of members in group discussions and the results of the group with good quality, which ultimately affect the increasing learning results in learning Study Curriculum Development.